PENGARUH KOMPOSISI BIODIESEL TERHADAP KINERJA MESIN DAN EMISI GAS BUANG - Djamin, Martin; S.Wirawan, Soni (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Renewable energy sources make a distinction as a promising solution towardssustainable and environmentally friendly energy production. Developing biodiesel isvery important for Indonesia due to various reasons including the abundanceavailability of the raw materials; an alternative renewable fuel to strengthen thecountry energy security and it is a solution to improve local air quality in severalIndonesian major cities. Biodiesel offers a realistic short-term alternative tosubstitute fossil fuels, and it will also be a necessary addition to the emissionfree technology for the future. This paper is intended to provide assessment andinvestigation of the use of different composition of biodiesel and its impact to theenvironment.Key words: Energy security, renewable energy, Biodiesel.